Strategi Inovasi Produksi dan Kompetitif Bisnis dalam Perspektif Islam - Ismail Nawawi (AL-TAHRIR, 2012)
Many new products fail in the market for one simple reason, that consumers do not want them. Then the company is obliged to develop products based on market demand. In connection with the phenomenon of the business, a company in Jombang, East Jawa, Indonesia, named Karya Kerja Sejahter Jombang (KKSJ), has been promoting innovation in production, anticipated the changes and dynamics of the business, enhanced market research, and identified business opportunities, desires and expectations of consumers as a first step in the innovation of production. This study was conducted to understand, describe and analyze the strategy of product innovation and the implementation in the growing competition in the enterprise business. The research data obtained from in-depth interviews with company management, then analyzed using the concept of production-based market research combined with the concept ofagilemanagem ent and agilemanufacturing. Furthermore, this study concludes that the company has been able to bring the overall KKSJ management to agiylity in pursuing the strategy of innovation in production according to consumer needs and wants and has been able to encourage competition in the business. The strategy of production innovation involves the tasks of marketing, engineering, and manufacturing, combined with agility of management and agility of manufacturing. The synergy amongst each of these factors has reached Concurrent Engineering/CE. The strategy of product innovation has taken according to market forces and technological developments, which in turn encourages business competition.